A nonconforming pressure-robust finite element method for the Stokes equations on anisotropic meshes. (14th January 2021) - Apel, Thomas; Kempf, Volker; Linke, Alexander; Merdon, Christian
Abstract: Most classical finite element schemes for the (Navier–)Stokes equations are neither pressure-robust, nor are they inf-sup stable on general anisotropic triangulations. A lack of pressure-robustness may lead to large velocity errors, whenever the Stokes momentum balance is dominated by a strong and complicated pressure gradient. It is a consequence of a method, which does not exactly satisfy the divergence constraint. However, inf-sup stable schemes can often be made pressure-robust just by a recent, modified discretization of the exterior force term, using H(div) -conforming velocity reconstruction operators. This approach has so far only been analyzed on shape-regular triangulations. The novelty of the present contribution is that the reconstruction approach for the Crouzeix–Raviart method, which has a stable Fortin operator on arbitrary meshes, is combined with results on the interpolation error on anisotropic elements for reconstruction operators of Raviart–Thomas and Brezzi–Douglas–Marini type, generalizing the method to a large class of anisotropic triangulations. Numerical examples confirm the theoretical results in a two- and a three-dimensional test case.